Execução penal e disruptura do sistema legal: um olhar sobre a defesa no cumprimento da pena - Santos, Josianne Pagliuca dos (2023)
The present work seeks to identify human rights violations in Brazil, whether those rights were internally created, or treaties signed by Brazil, in the field of criminal execution, as well as pointing how different players can act to remedy some of these disruptions. In addition to the bibliographical analysis on the subject, qualitative empirical field research was also carried out, with documental analysis of judicial processes of cases that are presented, as examples, to show some of the violations that have already occurred and that may occur again in Brazil. Finally, there are suggestions of conducts that can be taken to minimize the problem and reflections that must be made so that there is an improvement in the penal system in general